Probing the interactions between DNA nucleotides and biocompatible liquids: COSMO-RS and molecular simulation study - Gonfa, G. (Elsevier B.V., 2018)
Ionic liquid (ILs) have been attracting significant attention as an alternative solvent for DNA extraction/purification and stabilization/storage. In this work, we investigated the interaction between DNA nucleotides and bio-base ILs to get insight into the effect of structural variations of the ILs on the ILs-DNA complex formations. COSMO-RS based quantum calculations and molecular simulation were used to investigate the interaction between the bio-base ILs and DNA nucleotides. Deoxyadenosine 5â² monophosphate (A), Deoxythymidyine 5â² monophosphate (T), Deoxycytidine 5â² monophosphate (C), Deoxyguanosine 5â² monophosphate (G) and their dimers were used to model DNA. 260 ILs (13 cations and 20 amino acid based anions) were evaluated. Activity coefficients at infinite dilution of the DNA nucleotides and excess enthalpy of mixing of the systems were predicted using COSMO-RS model. Solvation free energies of the DNA nucleotides were estimated employing molecular dynamics simulations. The activity coefficients of DNA nucleotides decrease with increasing nucleotides chain length. This implies solubility of the nucleotides is higher for longer DNA nucleotide chain. Piperidinium and pyrrolidinium based ILs show lower activity coefficient than choline and morpholinium based ILs. ILs with anions containing nonpolar side chain amino acids show lower activity coefficient compared to those with polar side chains. This implies strong interaction between the nucleotides and ILs with anions containing nonpolar side chain amino acids compared to anions with polar side chains. Moreover, ILs based on anions with nonpolar side chain show higher negative excess enthalpy of mixing compared to those with polar side chain. Further, solvation free energies of DNA nucleotides in the ILs are negative. Solvation free energy is more negative for dimers compared to monomer nucleotides. ILs based on anions with nonpolar side chain show more negative solvation free energies compared to those with polar side chains. Â© 2017